Competition vs. Regulation in Mobile Telecommunications - Johan Stennek; Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2006)
This paper questions whether competition can replace sector-specific regulation of mobile telecommunications. We show that the monopolistic outcome prevails independently of market concentration when access prices are determined in bilateral negotiations. A light-handed regulatory policy can induce effective competition. Call prices are close to the marginal cost if the networks are sufficiently close substitutes. Neither demand nor cost information is required. A unique and symmetric call price equilibrium exists under symmetric access prices, provided that call demand is sufficiently inelastic. Existence encompasses the case of many networks and high network substitutability.
Keywords: L51; L96; 330; Network Competition; Two-way Access; Access Price Competition; Entry; Regulation; Network Substitutability; Mobiltelefon; Netzwerk; Preiswettbewerb; Gleichgewichtsstabilität; Regulierung; Spieltheorie